HMGA2, but not HMGA1, is overexpressed in human larynx carcinomas. Issue 7 (9th March 2018) - Palumbo, Antonio; De Martino, Marco; Esposito, Francesco; Fraggetta, Filippo; Neto, Pedro N; Valverde Fernandes, Priscila; Santos, Izabella C; Dias, Fernando L; Nasciutti, Luiz E; Meireles Da Costa, Nathalia; Fusco, Alfredo; Ribeiro Pinto, Luís Felipe
Abstract : Aims: Malignant tumours from the upper aerodigestive tract are grouped collectively in the class of head and neck squamous cell carcinoma (HNSCC). The head and neck tumours were responsible for more than 500 000 cancer cases in 2012, accounting for the sixth highest incidence rate and mortality worldwide among all tumour types. Laryngeal squamous cell carcinoma (LSCC) possesses the second highest incidence rate among all HNSCC. Despite significant advances in surgery and radiotherapy during the last few decades, no treatment has been shown to achieve a satisfactory therapeutic outcome and the mortality rate of LSCC is still high, with a 5‐year survival rate of 64%. Therefore, further investigations are required to identify the pathogenesis of LSCC. Methods and results: In order to search for new LSCC biomarkers, we have analysed the expression of the HMGA family members, HMGA1 and HMGA2, by quantitative reverse transcription–polymerase chain reaction (qRT–PCR) and immunohistochemistry. HMGA proteins are usually absent in the healthy adult tissues. In contrast, their constitutive expression is a feature of several neoplasias, being associated with a highly malignant phenotype and reduced survival. Here, we report HMGA2 overexpression in larynx carcinomas. Conversely, HMGA1 does not show any differences in its expression between normal and carcinoma tissues. Interestingly, HMGA2 overexpression appears associated with that of two HMGA1 ‐pseudogenes, HMGA1P6 and HMGA1P7, acting as a sponge for HMGA1‐ and HMGA2‐targeting microRNAs and involved in several human cancers. Conclusions: Therefore, HMGA2 overexpression appears to be a strong feature of larynx carcinoma, supporting its detection as a valid tool for the diagnosis of these malignancies.